Analisis PENGARUH JUMLAH ANGGOTA DAN MODAL TERHADAP SHU KOPERASI SERBA USAHA DI KECAMATAN ABIANSEMAL BADUNG - Triana Sulaksana, Ida Bagus; Bagus Indrajaya, I Gusti (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 8 No 11 (2019): Vol. 8, No.11, November 2019, pp (2501-2806), 2019)
Cooperatives are one of the economic forces that drive the growth of the national economy. The purpose of this study was to determine the analysis of the number of members, capital of SHU all-round cooperatives in the District of Abiansemal, Regency / City of Badung. The analytical tool used in this study is multiple linear regression which aims to determine the effect of independent variables which include the number of members and capital towards SHU. The data in this study are secondary data obtained from cooperative services and UMKM Badung districts / cities. The method in sampling uses the Slovin formula to show data in the sample. Based on the results of the study it was found that the number of members and capital simultaneously had a positive and significant effect on SHU. While the number of members partially has no effect on SHU and for capital partially has a positive and significant influence on SHU. The analysis of the factors tested in the study shows that the variable that has the dominant influence on SHU is the capital variable of the Multipurpose Cooperative in Abiansemal District. Keywords: number of member, capital, the remainder of the proceeds